Reckoning with Homelessness - Hopper, Kim (The Anthropology of Contemporary Issues, 2014)
"It must be some kind of experiment or something, to see how long people can live without food, without shelter, without security."-Homeless woman in Grand Central StationKim Hopper has dedicated his career to trying to address the problem of homelessness in the United States. In this powerful book, he draws upon his dual strengths as anthropologist and advocate to provide a deeper understanding of the roots of homelessness. He also investigates the complex attitudes brought to bear on the issue since his pioneering fieldwork with Ellen Baxter twenty years ago helped put homelessness on the public agenda.Beginning with his own introduction to the problem in New York, Hopper uses ethnography, literature, history, and activism to place homelessness into historical context and to trace the process by which homelessness came to be recognized as an issue. He tells the largely neglected story of homelessness among African Americans and vividly portrays various sites of public homelessness, such as airports. His accounts of life on the streets make for powerful reading